Implementation of the Scaffolding Method in Improving Zakat Material Learning Outcomes at SD Negeri 091265 Dolok Malela - Saragih, Desi Asmiani; Susanti, Eva; Murianto; lubis, Affrida Yani; Rahimah (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to analyze the application of the scaffolding method in improving learning outcomes of zakat material for grade VI students of SD 091265 Dolok Malela. The scaffolding method is a learning strategy that provides gradual support to students according to their needs until they are able to understand and master the material independently. This study uses a quantitative approach with an experimental method, involving two groups of students: an experimental group that is given learning using the scaffolding method and a control group that uses conventional methods. Data collection was carried out through learning outcome tests before and after treatment and observations during the learning process. Data analysis showed that students in the experimental group experienced a more significant increase in understanding compared to the control group. The results of this study confirm that the application of the scaffolding method can help students understand the concept of zakat better, increase their involvement in the learning process, and motivate them to be more active in exploring the material. Thus, the scaffolding method has proven effective in improving student learning outcomes and can be used as an alternative to a more interactive learning strategy in elementary schools, especially in Islamic Religious Education subjects. The recommendation from this study is for teachers to apply the scaffolding method more widely in learning to improve the quality of student understanding and provide support that is appropriate to their level of cognitive development